2019
DOI: 10.3748/wjg.v25.i30.4158
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with inflammatory bowel disease: Updated review of the therapeutic landscape

Abstract: High-quality data remains scarce in terms of optimal management strategies in the elderly inflammatory bowel disease (IBD) population. Indeed, available trials have been mostly retrospective, of small sample size, likely owing to under-representation of such a population in the major randomized controlled trials. However, in the last five years, there has been a steady increase in the number of published trials, helping clarify the estimated benefits and toxicity of the existing IBD armamentarium. In the Everh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 74 publications
0
22
0
2
Order By: Relevance
“…35 However, infliximab is also associated with potentially severe adverse events including an increased risk of opportunistic infection and infusion reactions, 36 and there are concerns about its use in elderly patients. 37 Both the aforementioned meta-analyses found that there were no significant differences between infliximab and ciclosporin in terms of drug-related adverse events, serious adverse events, or mortality. 14,33 Our results also demonstrated no significant differences between the two drugs in terms of serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, infliximab is also associated with potentially severe adverse events including an increased risk of opportunistic infection and infusion reactions, 36 and there are concerns about its use in elderly patients. 37 Both the aforementioned meta-analyses found that there were no significant differences between infliximab and ciclosporin in terms of drug-related adverse events, serious adverse events, or mortality. 14,33 Our results also demonstrated no significant differences between the two drugs in terms of serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…33 Unfortunately, however, faecal calprotectin is not validated in the elderly population, mostly because FC levels can increase also in the setting of other diseases, as well as under treatment with certain drugs, such as proton pump inhibitors and non-steroidal anti-inflammatory drugs, which are commonly used in the elderly TA B L E 1 Characteristics of patients who achieved (responders) or did not achieve (non-responders) mucosal healing population. 34,35 Thus, faecal calprotectin specificity might be low in the elderly population. 35 The T3/T4 ratio has been described as an independent marker of frailty in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Thus, faecal calprotectin specificity might be low in the elderly population. 35 The T3/T4 ratio has been described as an independent marker of frailty in elderly patients. 20 Despite no previous studies had evaluated this biomarker in IBD patients, a recent review showed that frail elderly patients are more susceptible to the complications of IBD and display lower healing capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations